(untitled) (European Journal of Pure and Applied Mathematics, 2012)
The main purpose of this article is to provide probabilistic proofs of the relationships betweenÂ the generalized Bernoulli (or Norlund) polynomials B()Â n (x) and the generalized Euler polynomialsÂ E()Â n (x) of (real or complex) order and degree n in x, which were proved recently by SrivastavaÂ and Pintér [11]. Some other approaches to these relationships and their seemingly interesting generalizationsare also investigated.